Letter: what explains improved survival from statin exposure after liver transplantation? Authors' reply. Issue 10 (21st October 2022) - Becchetti, Chiara; Dirchwolf, Melisa; Schropp, Jonas; Berzigotti, Annalisa; Bosch, Jaime
Abstract : LINKED CONTENT This article is linked to Becchetti et al papers. To view these articles, visit https://doi.org/10.1111/apt.17192 and https://doi.org/10.1111/apt.17228